Impulsive Fashion Purchases on Shopee: Fashion Involvement, Positive Emotions, Platform Quality, and Online Promotions - Aisyah Putri Agustin; Anton Agus Setyawan (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the factors influencing impulsive buying behavior among consumers using the Shopee marketplace, focusing on the fashion segment, which has experienced rapid growth, contributing significantly to revenue with an increase of up to 24% (Sritanakorn & Nuangjamnong, 2021). Increased income and accessible credit options have escalated impulsive buying tendencies, driven by consumers’ desire to fulfill immediate needs with ease (Park et al., 2006). The study examines the impact of consumer fashion involvement, positive emotions, online platform quality, and online sales promotions on impulsive buying behavior. Using a quantitative approach, data were collected through online questionnaires distributed to 208 purposively sampled respondents and analyzed with Structural Equation Modeling (SEM) using Smart PLS. The findings reveal significant direct effects of fashion involvement, positive emotions, online platform quality, and sales promotions on impulsive buying behavior, alongside potential mediating and interacting effects, such as positive emotions amplifying the influence of platform quality and sales promotions. These results highlight the importance of synergistic promotional strategies and user-friendly platform designs in stimulating impulsive purchases, while also acknowledging limitations in sample representativeness and suggesting further investigation into causal mechanisms and interactions between these factors to provide nuanced insights for e-commerce strategies.